1996
DOI: 10.1007/bf00188473
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colorectal resection

Abstract: Laparoscopy seems to offer the possibility of minimally invasive treatment, but long-term follow-up is needed to evaluate the efficacy of laparoscopic surgery in the treatment of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The early reports of port-site metastases concerned patients with advanced tumors and were probably the outcome of extensive tumor manipulation during surgery [11]. Many of these recurrences emerged shortly after surgery, suggesting the likelihood of neoplastic cell exfoliation during the procedure [11,13,14]; floating tumor cell implantation has also been demonstrated in experimental models [15]. The most recent series, however, show that this complication has the same low incidence after laparoscopy as after laparotomy [3,4,9,11,[16][17][18][19] and many authors reported no such occurrences at all [3,4,17].…”
Section: Discussionmentioning
confidence: 99%
“…The early reports of port-site metastases concerned patients with advanced tumors and were probably the outcome of extensive tumor manipulation during surgery [11]. Many of these recurrences emerged shortly after surgery, suggesting the likelihood of neoplastic cell exfoliation during the procedure [11,13,14]; floating tumor cell implantation has also been demonstrated in experimental models [15]. The most recent series, however, show that this complication has the same low incidence after laparoscopy as after laparotomy [3,4,9,11,[16][17][18][19] and many authors reported no such occurrences at all [3,4,17].…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for converting laparoscopic surgery to open surgery is obesity, leading most surgeons to consider morbid obesity a relative contraindication for laparoscopic colorectal resections [16,17]. The BMI is an objective index that can determine the presence of morbid obesity (defined as BMI > 30) [18].…”
Section: Discussionmentioning
confidence: 99%
“…All patients in both groups received pain relief by means of continuous epidural anesthesia (mepivacaine hydrochloride plus buprenorphid hydrochloride) and as-needed intramuscular injections of pentazocine. Two patients (11.1%) in the minilaparotomy group required pentazocine (30 mg and 15 rag, respectively); seven patients (70.0%) 12 [10,12] 16 [11,17] Values are expressed as the median, with the lower quartile and the upper quartile in brackets. Statistical analyses were conducted by the Mann-Whitney test.…”
Section: Postoperative Eventsmentioning
confidence: 99%
“…METHODS: The Italian Registry of Laparoscopic Colorectal Surgery database was analyzed to obtain data on cancer patients with abdominal wall recurrence, concomitant local or distant metastases, and interval between initial surgery and diagnosis of trocar site or minilaparotomy recurrences. 8 In the early 1990s alarming reports on early AWR at the trocar sites as well as at minilaparotomy after laparoscopic resection for colorectal cancer were published. RESULTS: From January 1992 to July 2000, 2,583 patients (1,753 cases of carcinomas and 830 cases of benign diseases) were recorded.…”
mentioning
confidence: 99%